2007
DOI: 10.1016/j.jalgebra.2006.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Cartan subalgebras of root-reductive Lie algebras

Abstract: Root-reductive Lie algebras are direct limits of finite-dimensional reductive Lie algebras under injections which preserve the root spaces. It is known that a root-reductive Lie algebra is a split extension of an abelian Lie algebra by a direct sum of copies of finite-dimensional simple Lie algebras as well as copies of the three simple infinite-dimensional root-reductive Lie algebras sl_infty, so_infty, and sp_infty. As part of a structure theory program for root-reductive Lie algebras, Cartan subalgebras of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…If g is root reducible, we are given an abelian subalgebra h = lim − → h n . Such subalgebras h ⊂ g are known as splitting maximal toral subalgebras of g. These subalgebras are also Cartan subalgebras of g, according to the definition and results in [DPS,Section 3]. We will simply use the term "Cartan subalgebra" when referring to splitting maximal toral subalgebras.…”
Section: A K-algebramentioning
confidence: 99%
“…If g is root reducible, we are given an abelian subalgebra h = lim − → h n . Such subalgebras h ⊂ g are known as splitting maximal toral subalgebras of g. These subalgebras are also Cartan subalgebras of g, according to the definition and results in [DPS,Section 3]. We will simply use the term "Cartan subalgebra" when referring to splitting maximal toral subalgebras.…”
Section: A K-algebramentioning
confidence: 99%
“…In [4] the uniqueness issue was discussed for gl(∞, C), sl(∞, C), and sp(∞, C), but not for so(∞, C). In the orthogonal setting one can have three different self-taut generalized flags with the same stabilizer (see [3] and [7], where the non-uniqueness is discussed in special cases.) Theorem 2.8.…”
Section: C Complex Parabolic Subalgebrasmentioning
confidence: 99%
“…In [3] it is shown that we cannot expect a 1-1 correspondence between maximal, locally solvable subalgebras and maximal generalized flags in this generality. Moreover, the work of Dan-Cohen in [1] shows that we cannot even expect a 1-1 correspondence between maximal, locally solvable subalgebras and maximal, closed generalized flags in an arbitrary locally finite Lie algebra.…”
Section: Introductionmentioning
confidence: 99%